Developing concept mapping strategy to enhance eighth-grade students’ English background knowledge - Nicky Elvin Cristin Zendrato; Yasminar Amaerita Telaumbanua; Riswan Zega; Afore Tahir Harefa (Universitas Pendidikan Indonesia, 2025)
This research aims to develop a Concept Mapping Strategy to enhance the background knowledge of eighth-grade students in English learning at SMP Negeri 7 Gunungsitoli. The research was motivated by the observed difficulty among students in connecting background knowledge with new English materials, which is essential for effective language learning, especially under the Kurikulum Merdeka that promotes student-centered and contextual learning. To address this issue, a strategy was developed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), with an emphasis on integrating visual and structured learning tools. The product was validated by three experts, material, media, and language, which were categorized as “Very Worthy”. The implementation stage was conducted through two cycles of Classroom Action Research (CAR), involving tests, classroom observations, and questionnaires. The results showed significant improvements: students’ average concept mapping scores increased, and test scores from Cycle I to Cycle II rose. Furthermore, both teacher and student responses indicated high levels of practicality. These findings demonstrate that the Concept Mapping Strategy is feasible, effective, and practical for enhancing students’ background knowledge and engagement in junior high school English classrooms. Abstrak Penelitian ini bertujuan untuk mengembangkan Strategi Pemetaan Konsep untuk meningkatkan pengetahuan latar belakang peserta didik kelas delapan dalam pembelajaran Bahasa Inggris di SMP Negeri 7 Gunungsitoli. Penelitian ini dimotivasi oleh kesulitan yang diamati di antara peserta didik dalam menghubungkan pengetahuan latar belakang dengan materi Bahasa Inggris baru, yang penting untuk pembelajaran bahasa yang efektif, terutama di bawah Kurikulum Merdeka yang mempromosikan pembelajaran yang berpusat pada peserta didik dan kontekstual. Untuk mengatasi masalah ini, sebuah strategi dikembangkan dengan menggunakan model ADDIE (Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi), yang menekankan integrasi alat pembelajaran visual dan terstruktur. Produk tersebut divalidasi oleh tiga ahli materi, media, dan bahasa dengan kategori “Sangat Layak”. Tahap implementasi dilakukan melalui dua siklus Penelitian Tindakan Kelas (PTK), yang melibatkan tes, observasi kelas, dan kuesioner. Hasilnya menunjukkan peningkatan yang signifikan: skor pemetaan konsep rata-rata peserta didik meningkat dan skor tes dari Siklus I ke Siklus II naik. Lebih lanjut, respons guru dan peserta didik menunjukkan tingkat kepraktisan yang tinggi. Temuan ini menunjukkan bahwa Strategi Pemetaan Konsep layak, efektif, dan praktis untuk meningkatkan pengetahuan dasar dan keterlibatan peserta didik dalam pembelajaran Bahasa Inggris di sekolah menengah pertama. Kata Kunci: pembelajaran bahasa Inggris; pengetahuan latar belakang; strategi pemetaan konsep